Future efficacy of pre‐emergence herbicides in corn (Zea mays) is threatened by more variable weather. Issue 6 (20th February 2021) - Landau, Christopher A; Hager, Aaron G; Tranel, Patrick J; Davis, Adam S; Martin, Nicolas F; Williams, Martin M
Abstract: BACKGROUND: By 2050, weather is expected to become more variable with a shift towards higher temperatures and more erratic rainfall throughout the U.S. Corn Belt. The effects of this predicted weather change on pre‐emergence (PRE) herbicide efficacy have been inadequately explored. Using an extensive database, spanning 252 unique weather environments, the efficacy of atrazine, acetochlor, S ‐metolachlor, and mesotrione, applied PRE alone and in combinations, was modeled on common weed species in corn ( Zea mays L.). RESULTS: Adequate rainfall to dissolve the herbicide into soil water solution so that it could be absorbed by developing weed seedlings within the first 15 days after PRE application was essential for effective weed control. Across three annual weed species, the probability of effective control increased as rainfall increased and was maximized when rainfall was 10 cm or more. When rainfall was less than 10 cm, increasing soil temperatures had either a positive or negative effect on the probability of effective control, depending on the herbicide(s) and weed species. Herbicide combinations required less rainfall to maximize the probability of effective control and had higher odds of successfully controlling weeds compared with the herbicides applied individually. CONCLUSIONS: Results of this study highlight the importance of rainfall following PRE herbicide application. As rainfall becomes more variable in future, the efficacy of common PRE herbicides will likely decline. However, utilizing combinations of PRE herbicides along with additional cultural, mechanical, biological, and chemical weed control methods will create a more sustainable integrated weed management system and help U.S. corn production adapt to more extreme weather. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Rainfall and soil temperature within the first 15 days after pre‐emergence application had varying effects on control of three key weeds in corn with six herbicides and herbicide combinations.